THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND SCHOOL ENVIRONMENT ON ENTREPRENEURIAL INTERESTS OF STUDENTS AT SMKN 7 KAB. TANGERANG - Sugoni Sugoni; M. Havidz Aima; Ikramina Larasati Hazrati Havidz (Dinasti International Journal of Education Management And Social Science, 2022)
The purpose of this research is to reveal and explain: (1) the effect of entrepreneurship education on interest in entrepreneurship, (2) the influence of the school environment on interest in entrepreneurship, and (3) the simultaneous influence of entrepreneurship education and school environment on interest in entrepreneurship. This research is a quantitative description using data collection techniques filling out a questionnaire. The population in this case is students of SMKN 7 Tangerang Regency with a sample of 87 respondents obtained from sample measurements using Slovin theory and data analysis methods using SEM PLS. The results of the study revealed that: (1) entrepreneurship education had no significant effect on interest in entrepreneurship, (2) school environment had a significant effect on interest in entrepreneurship, and (3) simultaneously entrepreneurship education and school environment had a significant effect on interest in entrepreneurship. Based on the correlation matrix analysis between dimensions, the highest correlation is the physical dimension and the non-physical dimension, therefore to increase interest in entrepreneurship is to improve the dimensions of growing awareness because it is a lever factor, can increase the value of entrepreneurial desire which in the end will significantly increase interest entrepreneurship.